Sitting intention in open spaces using the theory of reasoned action - Movahedfard, Atefeh (2012)
This study addresses the factors affecting sitting intention in open spaces based on the Theory of Reasoned Action. Theory of Reasoned Action is one of the important and related theories that researchers used for measuring behavioural actions. According to the theory and based on previous studies, this research used three variables, comfort, safety, accessibility, for finding the relation among these variables with attitude towards sitting intention in open spaces. Public spaces are perceived as being physically open and accessible to the general public that can help to promote a better relationship between students and their campus. Public spaces in campuses have a responsibility to provide usable, accessible open space for the users. One of the important features in campus open spaces is seating. Good seating opportunities enable numerous activities such as eating, reading, playing chess, watching people and talking, and these make open spaces attractive. Therefore, seating which enable these activities is vital to increase the quality of university campus’s open spaces. Furthermore, seating allows people to linger and enjoy the presence of students directly or indirectly, along with the sights, sounds and smells of a space. The methods for this study were observation, site visits, photography and survey. The survey is based on questionnaire of students in the Universiti Teknologi Malaysia. A total of 310 questionnaires were distributed among students, and then collected 309 respondents’ answers of which 306 were usable questionnaires. The results indicated that the two components of the Theory of Reasoned Action, attitude and subjective norm were positively and significantly related to sitting intention in open spaces. Moreover, the findings of this study indicated that comfort, safety, accessibility had positively and significantly related to attitude towards sitting intention in university campus open spaces